Cardiodiagnostic sex-specific differences of the female athlete in sports cardiology - Patel, V. I.; Gradus-Pizlo, I.; Malik, S.; El-Farra, A. B.; Dineen, E. H. (American Heart Journal Plus: Cardiology Research and Practice, 2022)
The cardiovascular care of highly active individuals and competitive athletes has developed into an important focus within the field of sports medicine. An evolving understanding of exercise-induced cardiovascular remodeling in athletes has led to a more robust characterization of physiologic adaptation versus pathological dysfunction, but this distinction is often challenging due to diagnostic commonalities. Current data reflects sporting-focused analyses of mainly male athletes, which may not be easily applicable to the female athletic heart. Increasingly female-specific cardiac dimensional and physiologic data are starting to emerge from comparative studies that may be utilized to address this growing need, and further guide individualized care. Here, we review current literature evaluating female-specific cardiovascular adaptations of the athletic heart, and formulate a discussion on cardiac remodeling, cardiodiagnostic findings, etiologic mechanisms, limitations of currently available data, and direction for future research in the cardiovascular care of female athletes.